Advancements in phase change materials in asphalt pavements for mitigation of urban heat island effect: bibliometric analysis and systematic review - Pinheiro, Claver Giovanni Silveira (2023)
This research presents a dual-pronged bibliometric and systematic review of the integration of phase change materials (PCMs) in asphalt pavements to counteract the urban heat island (UHI) effect. The bibliometric approach discerns the evolution of PCM-inclusion asphalt research, highlighting a marked rise in the number of publications between 2019 and 2022. Notably, Chang’an University in China has emerged as a leading contributor. The systematic review addresses key questions like optimal PCM types for UHI effect mitigation, strategies for PCM leakage prevention in asphalt, and effects on mechanical properties. The findings identify polyethylene glycols (PEGs), especially PEG2000 and PEG4000, as prevailing PCMs due to their wide phase-change temperature range and significant enthalpy during phase transitions. While including PCMs can modify asphalt’s mechanical attributes, such mixtures typically stay within performance norms. This review emphasises the potential of PCMs in urban heat management and the need for further research to achieve optimal thermal and mechanical balance